Aspek Organologis dan Musikologis Suling Kebyar - I Ketut Yasa (LP2M ISBI Bandung, 2018)
ABSTRACTSuling kebyar (kebyar flute) is a flute that is used in a Gong Kebyar ensamble. Gong Kebyar can be interpreted as a gamelan in which it plays using the system of